Favorable effect of glycoprotein IIbIIIa inhibitors among STEMI patients treated with primary PCI and incomplete ST resolution. (2nd January 2020) - Somaschini, Alberto; Cornara, Stefano; Ferlini, Marco; Crimi, Gabriele; Camporotondo, Rita; Gnecchi, Massimiliano; Ferrario Ormezzano, Maurizio; Oltrona Visconti, Luigi; De Ferrari, Gaetano M.; De Servi, Stefano
Abstract: Incomplete ST resolution after primary percutaneous coronary interventions (pPCI) in STEMI patients is a well known prognostic marker, associated with the occurrence of microvascular obstruction and increased mortality. The effects of the use of glycoprotein IIbIIIa inhibitors (GPIs) in this peculiar subset of high- risk patients is still unknown. The aim of the present study was to assess whether the GPIs administration would result in improved outcome in ST elevation myocardial infarction (STEMI) patients with incomplete ST resolution (ISTR). All consecutive STEMI patients who underwent pPCI at our hospital between 2005 and 2014 were enrolled (n = 2001). ST resolution was defined as incomplete with a < 70% resolution of initial ST shift. Mortality analyses were performed by Kaplan-Meier curves, multivariable analysis through Cox regressions and propensity matching score. The incidence of ISTR was 29% (n = 592). Among ISTR patients, GPIs use was an independent predictor of better prognosis (HR 0.39, 95% CI 0.16–0.96, p < 0.04). Propensity matched analysis confirmed that the use of GPIs was associated with a lower 30-day (6.1% vs 13.4%, p = 0.02) and 1-year (8.4% vs 15.1%, p = 0.045) mortality. STEMI patients treated with pPCI and presenting ISTR show a poor outcome. The use of GPIs in these patients is associated with improved survival at 30 days and at 1 year; the causes for these favorable effects remain speculative and could be related to the development and evolution of microvascular obstruction.